KONSEPSI ISLAM DALAM PENEGAKAN KEADILAN - Sangkot Nasution (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
Justice has always been regarded as the cardinal virtue and is a moral obligation that binds members of society. Justice is a goal to be achieved by law. Justice in this case implies "impartiiality" which in turn gives birth to the idea of equality (equality) which in turn is intended equality in treatment ".Keywords: Konsepsio Islam, Justice Enforcement.